Chemical growth and study of low intensity sensing ability of nanobranch and nanorod structured SnO2 UV detector. Issue 1 (February 2022) - Marimuthu, G.; Saravanakumar, K.; Jeyadheepan, K.; Mahalakshmi, K.
Abstract: Ultra violet (UV) photodetector (PD) has been gaining attention in the fields of environment, medical, civil, and military realms, etc. In this report, nanostructured tin oxide (SnO2 ) thin films were deposited by a hot-wall nebulizer spray pyrolysis technique. The nanostructured SnO2 UV PDs were fabricated. The structural, optical, and surface morphological properties have been investigated using the characterizing techniques of XRD, UV, PL spectrophotometer, and FESEM, respectively. The growth mechanism of structural transformation from nanobranch (Nb) to nanorod (NR) structure was discussed extensively. The photoelectric properties of the fabricated devices were performed under UV light (365 nm wavelength). The PD devices responded to two bias voltage ranges of 0.0004 V and 0.5 V for Nb and NR devices, respectively. The reason behind its due to the influence of surface states in the material that has been explained. Based on the results, the as-fabricated devices detect low light intensity in the microwatt power range. The transient photoresponse profiles exhibit the abundant surface states formation in nanostructures which showed as persistent photocurrent. Quenching of photocurrent for NR PD was observed at 0.5 bias voltage. We attained large photosensitivity and low bias sensing ability of SnO2 PD devices which clearly indicate that the possibility of the development of environment monitor supported self-powered devices. Graphical Abstract: ga1 Highlights: SnO2 nanobranch (Nb) and nanorod (NR) nanostructures were grown by Hot-wall nebulizer spray pyrolysis technique. The growth mechanism of Nb and NR structured SnO2 was elucidated. The influence of surface states on the optical and electrical properties was compared based on the surface morphology. Quenching of photocurrent was obtained for the NR structured UV detector device. A larger photosensitivity of 44.6 was achieved at a low bias of 0.4 mV for the Nb structured PD device.